2017
DOI: 10.1073/pnas.1704328114
|View full text |Cite
|
Sign up to set email alerts
|

Neural basis for hand muscle synergies in the primate spinal cord

Abstract: Grasping is a highly complex movement that requires the coordination of multiple hand joints and muscles. Muscle synergies have been proposed to be the functional building blocks that coordinate such complex motor behaviors, but little is known about how they are implemented in the central nervous system. Here we demonstrate that premotor interneurons (PreM-INs) in the primate cervical spinal cord underlie the spatiotemporal patterns of hand muscle synergies during a voluntary grasping task. Using spike-trigge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
152
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(164 citation statements)
references
References 45 publications
12
152
0
Order By: Relevance
“…This supports the notion that the neuromuscular system has a modular organisation that simplifies the control problem [17,18]. Spinal circuitry consisting of a network of premotor interneurons and motor neurons may generate basic movement patterns by mediating the synergistic drive to multiple muscles [19,20]. Stimulation of interneuronal regions in the spinal cord shows that these microcircuits are organised into discrete modules, each generating a specific pattern of muscular forces [21,22].…”
Section: Introductionsupporting
confidence: 63%
“…This supports the notion that the neuromuscular system has a modular organisation that simplifies the control problem [17,18]. Spinal circuitry consisting of a network of premotor interneurons and motor neurons may generate basic movement patterns by mediating the synergistic drive to multiple muscles [19,20]. Stimulation of interneuronal regions in the spinal cord shows that these microcircuits are organised into discrete modules, each generating a specific pattern of muscular forces [21,22].…”
Section: Introductionsupporting
confidence: 63%
“…Accordingly, in this study, we examined the functional roles of the modularity as the constraint of neuromuscular control. Although to clarify the relationship between the muscle synergies extracted from EMG data based on the decomposing technique and the physiologically observed neuronal structure of the modularity [22,23,26] was beyond the scope of this paper, we demonstrated that modular controllers that would be represented by muscle synergies play various important roles in the coordination in the nervous system to generate desired motor behaviours. Previous findings have shown that muscle synergies were shared across behaviours with different biomechanical demands [11][12][13][14].…”
Section: Modularity In the Neuronal Circuitmentioning
confidence: 96%
“…In the present study, we constructed a descending neural network model with three intermediate layers representing neurons in the primary motor cortex (M1), spinal modules and motoneurons controlling individual muscles. Recent studies have provided evidence of modular controllers in the neuronal circuitry [15,[20][21][22][23]. Based on these studies, we regarded the modules as interneuronal circuitry in the spinal cord [2,22,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showing clear patterns of conditional transfer entropy between EMGs suggest the involvement of additional pathways that interconnect different motor neuron pools. A spinal network of interneurons interconnecting motor neuron pools within the spinal cord is involved in the coordination of muscle activity (Levine et al, 2014;Takei et al, 2017).…”
Section: Discussionmentioning
confidence: 99%